Fermion localization on a split brane - Chumbes, A. E.R. [UNESP]; Vasquez, A. E.O. [UNESP]; Hott, M. B. [UNESP] (American Physical Society (APS), 2011)
In this work we analyze the localization of fermions on a brane embedded in five-dimensional, warped and nonwarped, space-time. In both cases we use the same nonlinear theoretical model with a nonpolynomial potential featuring a self-interacting scalar field whose minimum energy solution is a soliton (a kink) which can be continuously deformed into a two-kink. Thus a single brane splits into two branes. The behavior of spin 1/2 fermions wave functions on the split brane depends on the coupling of fermions to the scalar field and on the geometry of the space-time. © 2011 American Physical Society.